The first South American sandownid turtle fromthe Lower Cretaceous of Colombia (2015)
Sandownids are a group of Early Cretaceous-Paleocene turtles that for several decades have been only known by cranial and very fragmentary postcranial elements. Here I report and describe the most complete sandownid turtle known so far, including articulated skull, lower jaw and postcranial elements, fromthe Early Cretaceous (upper Barremian-lower Aptian, >120 Ma), Paja Formation, Villa de Leyva town, Colombia. The new Colombian sandownid is defined here as Leyvachelys cipadi new genus, new species and because of its almost identical skull morphology with a previously reported turtle fromthe Glen Rose Formation, Texas, USA, both are grouped in a single and officially (ICNZ rules) defined taxon. Phylogenetic analysis including L. cipadi supports once again the monophyly of Sandownidae, as belonging to the large and recently redefined Pan-Chelonioidea clade. The morphology of L. cipadi indicates that sandownids were not open marine turtles, but instead littoral to shallow marine durophagous dwellers. Leyvachelys cipadi not only constitutes the first record of sandowinds in South America, but also the earliest global record for the group.